Primeiro registro de Rachiplusia nu (Guenée, 1852) (Lepidoptera: Noctuidae) sobrevivendo em soja Bt no Brasil - Nardon, Adriana C.; Mathioni, Sandra M.; Santos, Leandro V. dos; Rosa, Daniel D. (Entomological Communications, 2021)
Loopers are important defoliators in several crop species. Among the loopers attacking non-Bt soybean cultivars, Chrysodeixis includens (Walker, [1858]) was the most common. The use of trangenic Bt soybean in appromately 70% of the soybean fields in Brazil led to a decrease in the loopers in these fields. However, technical field specialists and soybean producers recently observed Plusiinae larvae damaging transgenic Bt soybean, posing a risk over the Bt technology. Therefore, the aim of this study was to identify and confirm the catterpillar species feeding on transgenic Bt soybean fields in Brazil. Larvae and soybean leaf samples were collected in 12 soybean-producing locations from four Brazillian States. Soybean leaf samples were tested to confirm whether they were transgenic Bt. Larvae were reared in artificial diet and submitted to feeding trials on non-transgenic and transgenic Bt soybean leaves. The species identification was perfomed by amplicon sequencing of the cytochrome oxidase I (COI) gene of eight larvae per local. All 12 populations fed in the transgenic Bt soybean and the sequencing analysis of COI determined that they belong to Rachiplusia nu (Guenée, 1852) with 100% similarity to the COI sequences available in NCBI for this species. These results suggest that the R. nu species is not controlled by the genetic modification event present in the tested soybean variety and highlights the need for additional looper management control strategies, such as insecticide application, for controlling this insect pest in transgenic Bt soybean.